Intricating connections: the role of ferroptosis in systemic lupus erythematosus - Guowang Zhao; Xinghai Li; Ying Zhang; Ying Zhang; Xingzi Wang; Li Deng; Juan Xu; Shumei Jin; Zan Zuo; Zan Zuo; Linting Xun; Linting Xun; et al. (Frontiers in Immunology)
Systemic lupus erythematosus (SLE) is a chronic inflammatory and autoimmune disease with multiple tissue damage. However, the pathology remains elusive, and effective treatments are lacking. Multiple types of programmed cell death (PCD) implicated in SLE progression have recently been identified. Although ferroptosis, an iron-dependent form of cell death, has numerous pathophysiological features similar to those of SLE, such as intracellular iron accumulation, mitochondrial dysfunction, lipid metabolism disorders and concentration of damage associated-molecular patterns (DAMPs), only a few reports have demonstrated that ferroptosis is involved in SLE progression and that the role of ferroptosis in SLE pathogenesis continues to be neglected. Therefore, this review elucidates the potential intricate relationship between SLE and ferroptosis to provide a reliable theoretical basis for further research on ferroptosis in the pathogenesis of SLE.